2020
DOI: 10.1021/acscatal.0c02795
|View full text |Cite
|
Sign up to set email alerts
|

Direct Look at the Electric Field in Ketosteroid Isomerase and Its Variants

Abstract: Enzymes catalyze a number of reactions with high efficiency and stereoselectivity. It is thought that strong, direct, and permanent electric fields within the active site of the enzyme contribute to the superb catalytic efficiency of enzymes. This effect is called electrostatic preorganization. Most often, electrostatic preorganization is analyzed by evaluating the local electric field at discrete points, such as a bond center, using, for example, vibrational Stark spectroscopy. However, the protein macromolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 65 publications
1
79
0
Order By: Relevance
“…In particular optimal alignment of electric elds with large eld strengths can directly affect the energy pro le of chemical reactions through the chemical bonds of the transition states that are well aligned, and thus can signi cantly change the reaction product selectivity and catalysis. 23,26,30,31,32,33,34 When we project the electric elds onto the water molecule chemical bonds as a proxy reaction, we nd that the electric eld alignment with the free O-H bonds of surface molecules increases by ~ 30 MV/cm over that of hydrogen-bonded waters in the inner droplet, with eld strengths which can certainly activate strong bonds or break weak chemical bonds altogether. Our works shows that the nature of chemical reactivity at the air-water interface is not just about structural organization, but about electronic organization at the interface, and supports recent work that has suggested an alternative explanation for surface pH involving charge transfer 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular optimal alignment of electric elds with large eld strengths can directly affect the energy pro le of chemical reactions through the chemical bonds of the transition states that are well aligned, and thus can signi cantly change the reaction product selectivity and catalysis. 23,26,30,31,32,33,34 When we project the electric elds onto the water molecule chemical bonds as a proxy reaction, we nd that the electric eld alignment with the free O-H bonds of surface molecules increases by ~ 30 MV/cm over that of hydrogen-bonded waters in the inner droplet, with eld strengths which can certainly activate strong bonds or break weak chemical bonds altogether. Our works shows that the nature of chemical reactivity at the air-water interface is not just about structural organization, but about electronic organization at the interface, and supports recent work that has suggested an alternative explanation for surface pH involving charge transfer 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In both the KSI and Diels-Alder reactions, we have shown that topologically similar electric fields correspond to similar barriers of the corresponding reaction [19,47]. Furthermore, we showed how fields only at discrete points (which is what is often computed/measured) do not fully capture a relationship to the reaction barrier [47]. Instead, a more global, 3-D geometry of the electric field around relevant bonds are predictive of the reactivity.…”
Section: Understanding the Optimal Electric Fieldmentioning
confidence: 82%
“…Indeed, both contributions are by definition intimately coupled for determining the reaction rates, as better chemical positioning should correlate with better electric field alignment. 43 , 44 In fact we found that the chemical positioning (i.e., the optimization of the active site base that interacts directly with the substrate) overwhelmingly improved the electric field alignments relative to the original design after 7 rounds of LDE of the catalytic base in KE07-R7. 27 …”
Section: Designed Enzymesmentioning
confidence: 87%